Lifelong learning and the Roma minority in the Western Balkans - Óhidy, Andrea; Forray, Katalin R. (Emerald Publishing Limited, 2023)
Access, attainment and success of Roma people in education and lifelong learning is one of the most urgent public policy issues in Europe. According to empirical data Roma people are the most underrepresented group in schools and other educational institutions. Lifelong Learning and the Roma Minority in the Western Balkans examines the education situation of Roma in the Western Balkans, providing an overview of the education policies for Roma in 5 EU-candidate and potential candidate countries: Albania, Bosnia-Hercegovina, Kosovo, Montenegro and Serbia. The book is an important contribution to the field of comparative education and informs educational leaders and practitioners in the Western Balkans and beyond.